Prophet Muhammad as a Catalyst for Social Change: Insights from Martin Lings and Annemarie Schimmel - Yulingga, Sevina Dwi; Mujiburrahem; Permatasari, Niken Ayu; Zuhdi, Fahmi Ali (Pustaka Peradaban, 2025)
This study examines Prophet Muhammad’s role as a transformative agent of social change through the perspectives of Martin Lings and Annemarie Schimmel, two prominent non-Muslim scholars. Beyond his religious leadership, Prophet Muhammad revolutionized 7th-century Arabian society by addressing social inequities, fostering inclusivity, and instituting enduring values of justice, equality, and compassion. In his work Muhammad: His Life Based on the Earliest Sources (1983), Lings portrays the Prophet as a charismatic reformer who advocated for social justice, dismantling tribal divisions and advancing human rights. Lings emphasizes the Prophet’s role in unifying a fragmented society through the ummah—a community bound by faith and equality—and promoting economic equity through zakat and the prohibition of usury. Schimmel, in And Muhammad Is His Messenger (1985), adopts a phenomenological approach, highlighting the Prophet’s integration of spiritual leadership with practical governance. She underscores his role in advancing women’s rights, eradicating systemic oppression, and establishing a moral framework based on divine values. The Constitution of Medina, she argues, was a groundbreaking socio-political contract that promoted a pluralistic and harmonious society. By examining Lings’ historical narrative alongside Schimmel’s spiritual and cultural insights, this study provides a nuanced understanding of Prophet Muhammad’s multidimensional legacy. It positions him as an exemplar of justice and unity, offering valuable lessons for contemporary societies struggling with inequality and division. This interdisciplinary exploration reveals the lasting impact of Prophet Muhammad’s leadership as a unifier and model for ethical governance, transcending both time and cultural boundaries.